PEMBUATAN WEBSITE UNTUK MEDIA PEMASARAN ONLINE PADA SAVANA ADVENTURE YOGYAKARTA - Hendra Kurniawan; Ika Nur Fajri (Batara Wisnu : Indonesian Journal of Community Services, 2024)
The Industrial Revolution 4.0 has changed the marketing models used by business actors, especially MSMEs (Micro, Small, and Medium Enterprises). By 2022, 21.8 million MSMEs had gone digital, utilizing the internet and online media. Savana Adventure, which acts as a partner, is an MSME involved in outdoor equipment rental, located at Jl. Banteng Utama II No. 82 C, Banteng, Sinduharjo, Ngaglik, Sleman, Yogyakarta. This MSME was founded in 2018 by three individuals who share a background as nature enthusiasts. Its main products include equipment for mountain climbing, camping, outbound activities, off-roading, and trail running. The partners also collaborate with various parties, such as other outdoor equipment providers, camping sites, tour guide services, and mountain climbing guides around Yogyakarta, to expand the range of services offered to consumers. Currently, the partners are facing challenges in marketing, particularly online. The large number of competitors in the same business sector makes it difficult for them to attract new customers. Despite various online marketing efforts, the impact has been minimal and not fully optimized. Therefore, there is a need for additional efforts to support the existing online marketing, such as creating a website. A website can enhance online marketing activities, build a strong brand image in the community, and facilitate communication between partners and consumers